Islamist Groups as Providers of Social Services for Children within the Palestinian Community in Israel - Magadlah, Haneen (Journal of ecumenical studies, 2021)
This essay aims to uncover the methods and strategies adopted by Islamist groups in the Arab community in Israel in providing social services for children. It describes the results of a case study that focuses on the observation of the work of two Islamic groups in Baqa al-Gharbiya, an Arab city in the immediate vicinity of the Green Line. The study adopts the methodology of qualitative research through in-depth interviews with sixty persons, including children. The characteristics of the services these groups provide will be identified, as well as the links among the organizations and with other community and government organizations. The results indicate that these Islamist groups have a significant presence and influence in the Arab community, as they are active in the political and social spheres comparable to Islamist social service providers in other countries in the Middle East. Palestinian Arab clients prefer to turn to the Islamist groups for help over public social services provided by Israel. When they reach out, it is easier to build trust due to their shared religious and social background. The Israeli institutions, by contrast, represent an intrusive, alien force that they associate with land expropriation and neglect in providing social services.